CHARACTERISTICS OF FACTORS AFFECTINGDEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP (Scientific journal of the Fergana State University, 2023)
This article theoretically examines approaches to the content and essence of small business and private entrepreneurship in the conditions of rapid development of economic relations. At the same time the main factors influencing the development of small business and private entrepreneurship are studied.